Mengintegrasikan Wahyu dan Akal dalam Pendidikan Islam Kontemporer - Ikhwan, Afiful (Chalim Journal of Teaching and Learning, 2024)
This study aims to philosophically examine the basic concept of Islamic education and how this foundation is applied in the practice of Islamic education in Indonesia, especially in Islamic-based elementary education institutions. Islamic education does not only aim to form intellectually intelligent humans, but also spiritually and morally whole. In the context of national education, Islamic education often experiences challenges in terms of integrating basic values ​​into formal-secular education systems and policies. This research method is qualitative with a field study approach at Madrasah Ibtidaiyah Baitul Muttaqiin Sumberagung, which was chosen because it is one of the areas with quite rapid development of Islamic educational institutions. The results of the study show that first, the basis of Islamic education in the perspective of Islamic philosophy includes ontological aspects (the nature of humans as creatures of God), epistemological (sources of knowledge from revelation and reason), and axiological (the purpose of education as worship and the achievement of perfect humans). Second, implementation in the field shows that there are efforts to integrate Islamic values ​​and the national curriculum, although there are still obstacles such as limited teacher resources and inconsistent policies. These findings serve as material for reflection to strengthen the philosophical foundations of the Indonesian Islamic education system.